Identity and Belonging in Na’ima B. Robert’s Boys vs Girls (2010) - Al-Janabi, Hazem Kamel Abd; Az-Zubaidy, Thamir R. S. (Journal of Ecohumanism, 2024)
This paper investigates Na’ima B Robert’s Boys vs Girls (2010), which relates the story of two children of a Pakistani-English family. It casts light on the impact of the parents’ Pakistani culture on their children, Farhana and Faraz, who are born in England, but inherited a cultural legacy, with which they have never established any direct contact. Accordingly, Robert’s novel deals with issues common in diasporic literature, namely, identity, alienation, and belonging. The paper examines their attempt to reconcile the two parts of their identity, Pakistani and English, and reduce the pernicious impacts of their feelings of alienation. While exploring the two children’s process of identity formation in Robert’s novel, we draw on scholars, such as Paul Gilroy, Stuart Hall, and Salman Rushdie, who, like Robert and the two main characters in this novel, face similar challenges in negotiating identity and expressing their sense of belonging. Further, we employ Avtar Brah’s analysis of the cultural constrains imposed on young Asian Muslims in educational institutes as we trace Farhana and Faraz’s endeavour to counter the stereotyped image of Muslims in the West while celebrating their Islamic culture at. Moreover, it depicts the parents’ concerns that their children’s espousal of their Islamic culture might negatively impact on their progress in the West. Depending on non-white feminists’ notions, namely Hazel Carby, the paper critiques white feminism which marginalises the needs and aspirations of non-white women residing in the west.